5(-5a+5)+4(5-a)=-13

Simple and best practice solution for 5(-5a+5)+4(5-a)=-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(-5a+5)+4(5-a)=-13 equation:



5(-5a+5)+4(5-a)=-13
We move all terms to the left:
5(-5a+5)+4(5-a)-(-13)=0
We add all the numbers together, and all the variables
5(-5a+5)+4(-1a+5)-(-13)=0
We add all the numbers together, and all the variables
5(-5a+5)+4(-1a+5)+13=0
We multiply parentheses
-25a-4a+25+20+13=0
We add all the numbers together, and all the variables
-29a+58=0
We move all terms containing a to the left, all other terms to the right
-29a=-58
a=-58/-29
a=+2

See similar equations:

| 8×2(-1+m)+3×2=2×2(m-2) | | 5x+2-2(x-1)=3x-4 | | 8x-5(x+9)=4x-5 | | Z=4/9t+4;t | | (x^2)=16 | | 5x2-25=100 | | .10d=4.95 | | x=4=20 | | -3x-47=-17 | | 24+12n=15n | | 0.75/2=3/m | | 4(x-3)=2x-9+1 | | (x-20)/4=5 | | 6x-2-8x=-12 | | 3.9+0.79x=1.09x | | (x^2)=2x | | 11=2x+10 | | 5x+31=11 | | 4.2=v/2.6 | | 5x-14=7x+26 | | 9(7x-3)=603 | | 13w-12w=5 | | 7x14-3x=30 | | 7x+2=2(2x+5) | | -7(x-2)+5(3-x)-4x=-12x+13 | | 8w+4-2(-5w-2)=4(w-1) | | 200=15h | | -79(x+8)=21 | | 9x+8+7x+6=0 | | 15m-8m=7 | | -69=-5x-4(x+6) | | 1.8y+1.4+0.7y=7.4+0.5y |

Equations solver categories